Essential Java for AP CompSci : from programming to computer science - Winnie, Doug (Apress, 2021)
Computer science has become a basic life skill that will impact almost every career, and it is a skill that anyone can learn. Whether you are going into a career or side hustle in business, technology, creativity, architecture, or almost any other field, you will find coding and computer science play a role. This book teaches you the essential skills for computer science using one of today's most popular programming languages, Java. Each lesson is designed to be completed in about an hour, giving you a step-by-step process to learn over time and integrate into your daily workflow and schedule. Whether you are a student starting out with computer science, or looking to reskill into a digital career, this text will help you dive into the fundamentals of programming and prepare yourself to jump start your journey into computer science. Inside you will learn: The primary building blocks of programming using the Java programming language Terminology and best practices of software development Object-oriented programming concepts Common-language definitions and examples to help drive understanding and comprehension of computer science fundamentals.